2010
DOI: 10.1126/science.328.5980.844
|View full text |Cite
|
Sign up to set email alerts
|

Malaria's Drug Miracle in Danger

Abstract: Like many others before it, the latest generation of malaria drugs is losing its punch. This time, can global disaster be averted?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
98
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 0 publications
1
98
0
Order By: Relevance
“…These results are in agreement with earlier studies in Nigeria that have shown both combinations to be safe and well tolerated [7,8,17] and are also consistent with the high cure rates that have been reported for ACT in other malaria-endemic areas of Africa [18][19][20]. Artemisinin and related endo-peroxide antimalarials act rapidly by clearing P. falciparum in the blood, thereby providing prompt therapy for severe infections [21]. Moreover, artemisinins are also active against parasites resistant to two major classes of antimalarials, quinolines and antifolates, thereby making them the most potent and effective antimalarials presently used [22].…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with earlier studies in Nigeria that have shown both combinations to be safe and well tolerated [7,8,17] and are also consistent with the high cure rates that have been reported for ACT in other malaria-endemic areas of Africa [18][19][20]. Artemisinin and related endo-peroxide antimalarials act rapidly by clearing P. falciparum in the blood, thereby providing prompt therapy for severe infections [21]. Moreover, artemisinins are also active against parasites resistant to two major classes of antimalarials, quinolines and antifolates, thereby making them the most potent and effective antimalarials presently used [22].…”
Section: Discussionsupporting
confidence: 82%
“…Second, isolation from the plant source is still the only practical means of accessing ART as a starting material, and with harvest and extraction costs being highly variable and often subsidy-driven, the supply of ART fluctuates widely (10). Finally, alarming reports of ACT treatment failures along the Thai-Cambodian border, and more recently, increased parasite clearance times with artesunate (AS) monotherapy, have raised significant concerns that resistance to these agents may be emerging (2,3).…”
mentioning
confidence: 99%
“…Herein we describe the exceptional pharmacokinetic and antimalarial properties of OZ439 (Fig. 1C) and the studies that led to its selection as a clinical development candidate (3,5,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Current malaria treatment relies heavily on artemisininbased combination therapies (2). Artemisinin and related endoperoxide antimalarials clear P. falciparum infections rapidly, providing prompt therapy for severe infections (3).…”
mentioning
confidence: 99%